A building's design quality: measuring the esoteric. Issue 1 (11th September 2018) - Zemke, Dina Marie; Zhong, Yun Ying; Raab, Carola
Abstract : Purpose: Firms that serve customers in the service environment rely on a well-designed servicescape. This is particularly true in the hotel industry, where the hotel's design is an important part of the product mix. However, despite design's importance, there is no common instrument available to measure hotel design quality. The purpose of this paper is to present a quantitative method, the Design Quality Indicator, to measure guests' evaluations of hotel design quality. Design/methodology/approach: Nearly 5, 000 guests of two full-service hotel brands were surveyed soon after a hotel stay (within two weeks of check-out). The DQI's factor structure is tested using principle components analysis and confirmatory factor analysis to improve the reliability, validity and parsimony of the instrument. Findings: The study yields a DQI instrument that is reduced from 92 to 41 measurement items, with good reliability and validity, enabling more efficient data collection and analysis. Research limitations/implications: This study only examines guests' assessments of two full-service hotel brands. The instrument can be used to explore design's relationship with numerous outcome variables, such as satisfaction, loyalty, and repatronage intentions, as well as property performance outcomes. Practical implications: The methods demonstrated can be used by hotel owners and operators to inform resource allocation decisions, particularly when planning for renovations. Originality/value: This study provides a reliable, validated quantitative assessment of hotel design quality. It is also one of the few studies that elicits feedback about a guest's actual hotel stay, rather than a hypothesized or simulated stay.